Implikasi Peran Orang Tua Dalam Mendukung Pembelajaran Pendidikan Agama Hindu Terhadap Kompetensi Anak Pada Masa Pandemi di Kota Denpasar - Sutriyanti, Ni Komang; Luwih, I Made; Darma Permana, I Dewa Gede (Jurnal Penelitian Agama Hindu, 2023)
The pandemic storm had succeeded in changing education directed online (into network). Over time, online learning raises various problems that are feared to have implications for children's competence. Moreover, online learning tends to focus on the role of parents as educators at home. Reflecting on this, this research chose schools in Denpasar as a sample to identify the role of parents on children's competencies during online implementation. As an important part of the research, several research objectives were formulated, namely, to find out the implications of the parents’ role on children's competence in the field of spiritual attitudes and social attitudes as a moral (affective) basis, the field of knowledge or children's analytical power (cognitive), and the field of creativity or skills child (psychomotor). By using a research method with a type of qualitative research, this research obtained data from primary and secondary data sources. In terms of determining informants, a purposive sampling technique was used, balanced with several data collection techniques, namely observation techniques, interviews, document recording, and library research. After data was obtained, the, data was analyzed using interactive data analysis techniques from Miles and Huberman. The results of this research indicated that the role of parents in learning Hindu Religious Education during pandemic in Denpasar city had positive implications for development of children's spiritual attitude competencies, but it had negative implications for development of children's social attitudes, knowledge and skills. So, conclusion of this research was the role of parents in online learning during the pandemic has been going well, but it needs to be optimized so that it has positive implications for the overall development of children's competencies.